Understanding public (mis)understanding of tDCS for enhancement - Cabrera, Laura Y.; Reiner, Peter B. (Frontiers in Integrative Neuroscience, 2015)
In order to gain insight into the public’s perspective on using the minimally invasive technique transcranial direct current stimulation (tDCS) as an enhancement tool, we analyzed and compared online comments in key popular press articles from two different periods (pre-commercialization and post-commercialization). The main conclusion drawn from this exploratory investigation is that public perception regarding tDCS has shifted from misunderstanding to cautionary realism. This change in attitude can be explained as moving from a focus on an emergent technology to a focus on its applications, benefits, and risks as the technology becomes more grounded within the public domain. Future governance of tDCS should include the concerns and enthusiasms of the public. Keywords: cognitive enhancement, neuroethics, public understanding, transcranial direct current stimulation, brain stimulation, public policy.